FACTORS AFFECTING INDONESIAN SHRIMP EXPORT TO JAPAN - Adhyaksa Eka Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study is aimed at knowing and explaining the effects of domestic shrimp production,the price of Indonesian shrimp exports and the exchange rate of rupiah on the volume ofIndonesian shrimp exports to Japan. This type of study is explanatory research using aquantitative approach. This study uses secondary data which is sequential data from2012-2016 in monthly form. Analysis of the data used is multiple linear regressionanalysis with the help of program eviews. The results of this study are domestic shrimpproduction, Indonesian shrimp export prices, and exchange rates simultaneously have asignificant effect on the volume of Indonesian shrimp exports to Japan. Meanwhile, onlydomestic shrimp production and Indonesian shrimp export prices have a partiallysignificant effect on the volume of Indonesian shrimp exports. Based on these results, it isrecommended that the Indonesian government maintain the quality of shrimp so thatIndonesian shrimp can compete in the international market.Keywords: volume of Indonesian shrimp exports to Japan, domestic shrimp production,Indonesian shrimp export prices, rupiah exchange rate